Penerapan Fuzzy Sugeno dalam Usaha Roti Ketawa - Sri Anita Siallagan; Windah Sahara (LPPM STIKOM Tunas Bangsa, 2020)
One of the food processing business that is much in demand by the community now is the laughing bread. The business that sells laughter bread products, Roti Ketawa Pelangi, is located in Jalan Sangnawaluh, the city of Pematangsiantar, North Sumatra province, where entrepreneurs in the Rainbow Laughter Bread are still having difficulty in determining the sales results for a week. This study aims to resolve the above problems by recommending a method. The method used in this study is the Sugeno fuzzy method. Data collection techniques conducted by researchers is a technique of direct interviews with an employee who is responsible for the business. In this study, the authors used 3 criteria including price, production, and sales. The results of this study are expected to provide input to business owners so they can count sales during the week.